Atlantic decadal-to-bidecadal variability in a version of the Kiel Climate Model - Sun, Jing; Latif, Mojib; Park, Wonsun (Climate Dynamics, 2023)
Atlantic decadal-to-bidecadal variability (ADV) is described from a multimillennial control integration of a version of the Kiel Climate Model (KCM). The KCM’s ADV is the second most energetic mode of long-term North Atlantic variability in that simulation, whereas the Atlantic multidecadal variability (AMV) is the leading mode that has been described in a previous study. The KCM’s ADV can be regarded as a mixed oceanic gyre-overturning circulation mode that is forced by the North Atlantic Oscillation. The extratropical North Atlantic sea surface temperature (SST) anomalies associated with the model’s ADV initially exhibit a tripolar structure in the meridional direction, which is linked to the gyre circulation. After some years, the SST-anomaly pattern turns into a monopolar pattern located in the subpolar North Atlantic. This transition is related to the overturning circulation. The AMV and the ADV co-exist and share some similarities. Both modes of variability rely on the upper-ocean heat transport into the subpolar North Atlantic. They differ in the importance of the gyre and overturning circulations. In the ADV, gyre and overturning-heat transports into the subpolar North Atlantic are equally important in contrast to the AMV where the overturning contribution dominates.